LoRa-IoT Focused System of Defense for Equipped Troops [LIFE] - .V, Shree Gowri Santhosh; .E, Vishal; .R, Vishak; Rahimunnisa, K. (Journal of Ubiquitous Computing and Communication Technologies, 2020)
National security is the capacity of a nation to mobilize military forces to guarantee its borders and successfully defend against physical threats including military aggression and attacks by enemy troops. Every country lives peacefully as soldiers perform their duties. Furthermore, soldiers safeguard's the honor of their country. Military communication plays an important role in nation's warfare. Military communication concerns with transmission of every information from reconnaissance as well as other groups in contact with opposition. There are several issues with respect to soldiers' safety. Whenever any soldier crosses the enemy lines, it is really essential for base station to identify the position and health condition of all the soldiers. This paper presents an idea of monitoring the soldier and also testing every soldier's health condition which helps army personnel to schedule the responsive operations. This paper includes an opportunity to map the positions and record the safety of the soldiers who get lost and wounded on the front line in real time. The data from sensors and GPS module will be transmitted wirelessly utilizing the soldiers' LoRa kit. The data gathered will be uploaded to the cloud for further statistical analysis. Upon receiving the health status of soldiers, the army officials can keep track of every soldier. Our proposed system allows army personnel at bivouac to track the current GPS position of every battalion and also checks the vitals such as body temperature, blood pressure, ECG, SpO2 of soldiers. It also consists an extra feature with the help of that soldier can ask for help manually by pressing an alert switch to inform the army personnel at bivouac if he is in need or may have sensed the enemy intrusion.
Keywords: LoRa; Health Monitoring; Enemy Intrusion; Wireless Sensor Networks; Military Communication; Base Station